Outsourcing and Firm-level Performance - Bernd Görzig; Andreas Stephan (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
Using firm-level panel data from the German cost structure survey over the period 1992 to 2000, our empirical analysis shows that firms that increased material inputs relative to internal labor costs performed better in terms of gross operating surplus than other firms. However, firms that increased external services relative to internal labor costs, thus outsourcing service functions previously provided within the firm, performed worse. In sum, our findings support the view that firms tend to overestimate the benefits accruing from outsourcing of services previously provided internally.
Keywords: L60; L23; L22; 330; Outsourcing; Firm Performance; Business Service Sector; Outsourcing; Unternehmensentwicklung; Rentabilität; Kostenstruktur; Unternehmensdienstleistung; Schätzung; Deutschland